Genealogia da biopolítica: uma leitura da analítica do poder de Michel Foucault - Luiz Felipe Martins Candido (2013)
From the 1970´s, stumbling upon some limitations of his previous work, Michel Foucault started his genealogical task-work, in which the problems of truth and the subjects, considered in their relations with cultural, social, economical and political practices were at stake. In thatmoment, Foucault was concerned about the complex relations between power and knowledge, and, resizing his researches, he gave them an eminently political character. He turns his attention to specific problems, in order to promote understanding on politics´ behaviour and power in modernity, guided by his interest in the present, with a critical-philosophical interrogation that intends to understand how do we become who we are. In this context, after producing studies concerning micropowers, Foucault conceives, in his conferences and courses at Collège de France and in the first volume of his Histoire de la sexualité [History of Sexuality], the notion of biopolitics, an idea which pursuits to apprehend the mode of power´s workout, characterized by the treatment of mass phenomena (births, mortality, health, hygiene, habitation...), or rather, of management of populations´ life. Aiming to pointing out a panorama of biopolitics´s emergence and the handling of the problem of biopolitics in Foucault´s proper thought, as well as proposing a biopolitical reading as a way of political power´s practices in modernity regarding the elaborations of the historian-philosopher, also noticing his detachment and critics about philosophical-juridical approaches concerning political sovereignty, we intend, firstly, an historical-philosophical characterization conducted by Foucault in his relations with the problem of truth and the production of subjects. Secondly, from the comprehension of his research methods, we suppose to enter his elaborations about historical objects on which he produces his studies, going through a discussion about the idea of disciplinary power and the problem of the norms, an essential point for biopolitics´ comprehension, also denominated by Foucault as a political anatomy of the body. Thirdly, we intend to perceive the development of Foucault´s problematization about power itself, and how he turns from a specific investigation regarding disciplinary power´s operation until achieve his theoretical formulations of power as government, then, hisup-growth considering political government and about the development of a governmental rationality with a consequent governmentalization of State, fundamental for the establishment of politics in modernity as biopolitics. At last, we attempt to offer a characterization of biopolitics´ notions considering two procedures: first, from the contrast between other concepts of biopolitics and Foucault´s one, and posteriorly, in this sense, presenting a description and an analysis of the main characteristics and problems discussed by Foucault in his analysis of biopolitics, highlighting the relation between biopolitics and sexuality,medicine, statistics and security and the problem of racism and State´s racism.